The collaborative mode by PmSVPs and PmDAMs reveals neofunctionalization in the switch of the flower bud development and dormancy for Prunus mume - Zhao, Kai; Zhou, Yuzhen; Zheng, Yan; Zheng, Rui-yue; Hu, Meijuan; Tong, Yan; Luo, Xianmei; Zhang, Yangting; Shen, Ming-li (Frontiers in Plant Science, 2022)
Prunus mume (Rosaceae, Prunoideae) serves as an excellent ornamental woody plant with a large-temperature-range cultivation scope. Its flower buds require a certain low temperature to achieve flowering circulation. Thus, it is important to delve into the processes of flower bud differentiation and dormancy, which affected its continuous flowering. These processes are generally considered as regulation by the MADS-box homologs, SHORT VEGETATIVE PHASE (SVP), and DORMANCY-ASSOCIATED MADS-BOX (DAM). However, a precise model on their interdependence and specific function, when acting as a complex in the flower development of P. mume, is needed. Therefore, this study highlighted the integral roles of PmDAMs and PmSVPs in flower organ development and dormancy cycle. The segregation of PmDAMs and PmSVPs in a different cluster suggested distinct functions and neofunctionalization. The expression pattern and yeast two-hybrid assays jointly revealed that eight genes were involved in the floral organ development stages, with PmDAM1 and PmDAM5 specifically related to prolificated flower formation. PmSVP1–2 mingled in the protein complex in bud dormancy stages with PmDAMs. Finally, we proposed the hypothesis that PmSVP1 and PmSVP2 could combine with PmDAM1 to have an effect on flower organogenesis and interact with PmDAM5 and PmDAM6 to regulate flower bud dormancy. These findings could help expand the current molecular mechanism based on MADS-box genes during flower bud development and dormancy.